The Effect of Temperature on Tribological Properties of Chemically Modified Bio-Based Lubricant - Zulkifli, Nurin Wahidah Mohd; Kalam, Md. Abul; Masjuki, Haji Hassan; Al Mahmud, K.A.H.; Yunus, R. (Taylor & Francis, 2014)
Vegetable oil has several characteristics that provide advantages for use as lubricant. This includes a high viscosity index, high flash point, high biodegradability, and friction and wear reduction properties. However, vegetable oil has some disadvantages such as low oxidation stability and low thermal stability. The transesterification process of palm oil using trimethylolpropane (TMP) alcohol has been proven to reduce the oxidation stability of vegetable oil. However, little research has been carried out on the effect of TMP ester as a lubricant in term of friction and wear. Therefore, this study investigated the effect of temperature on the tribological properties of TMP ester using a four-ball machine. The load and speed of the sample were set at 40 kg and 1,200 rpm, respectively. Temperature was varied between 50 and 100°C. It was found that TMP ester improved the friction properties by around 15-20%. At low temperature, TMP esters have a higher coefficient of friction (COF) compared to paraffin oil. However, as the temperature increased higher than 80°C, paraffin oil had a highere COF value. This is because at high temperature, the lubricant filmed formed by fatty acids tends to be less stable and breaks down more easily. © 2014 Copyright © Society of Tribologists and Lubrication Engineers.